Microbiological and Pharmacological Behavior of 7-Chlorolincomycin - Meyers, Burt R. (1969)
Replacement of the 7-(R) hydroxyl group of lincomycin by a 7-chloro-substituent produced a compound with greater in vitro activity than the parent. Laboratory studies of this compound showed it to be highly active against all of the following strains of gram-positive organisms examined, including penicillinase- and nonpenicillinase-producing staphylococci, Diplococcus pneumoniae, Streptococcus viridans and Streptococcus pyogenes. The enterococci, as well as all the gram-negative organisms tested, with the exception of some strains of Haemophilus, were uniformly insensitive to this agent. The activity of 7-chlorolincomycin was not affected by serum or inoculum size. Resistance developed in a slow stepwise pattern. Peak levels of approximately 2 μg/ml were achieved in the serum of volunteers after ingestion of 150 mg either in the fasting state or after a meal. No untoward effects were noted. The antibiotic appears to be of potential value in the treatment of infections due to gram-positive organisms, with the exception of enterococcus.